Molecular structure of the gene and the 5'-flanking region of the human lymphocyte immunoglobulin E receptor. - Suter, U (1987)
Overlapping clones which contain the complete gene encoding the human lymphocyte IgE receptor (MW:45kd; identical with CD23), were isolated from human genomic lambda-libraries. The gene spans approximately 13kb and comprises 11 exons. The 5'-end of the mRNA was mapped by primer extension and S1-mapping, revealing two initiation sites for transcription. Two corresponding TATA boxes were identified by sequencing the 5'-flanking region. A 188bp long inverted repeat was found which flanks the promoter region and could possibly be involved in gene regulation. Exons 9 to 11 code for the IgE-binding domain of the receptor which shows homology to several lectins, particularly to the asialoglycoprotein receptor. A comparison of the exon/intron arrangement of these genes implies that their lectin domains have evolved from a common ancestral cassette.